2022
DOI: 10.3390/membranes12020120
|View full text |Cite
|
Sign up to set email alerts
|

Sludge Derived Carbon Modified Anode in Microbial Fuel Cell for Performance Improvement and Microbial Community Dynamics

Abstract: The conversion of activated sludge into high value-added materials, such as sludge carbon (SC), has attracted increasing attention because of its potential for various applications. In this study, the effect of SC carbonized at temperatures of 600, 800, 1000, and 1200 °C on the anode performance of microbial fuel cells and its mechanism are discussed. A pyrolysis temperature of 1000 °C for the loaded electrode (SC1000/CC) generated a maximum areal power density of 2.165 ± 0.021 W·m−2 and a current density of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…These authors found that MFCs with sludge carbon electrodes, especially those obtained at a carbonization temperature of 1000 • C, exhibited improved performance in chemical oxygen demand removal efficiency, organic matter degradation, and electrochemical oxidation activity compared with carbon cloth electrodes. The sludge carbonization temperature significantly influenced MFC system voltage output, with sludge carbon electrodes consistently outperforming carbon cloth electrodes [177]. This can be seen in Figure 10.…”
Section: Microbial Fuel Cell Electrodesmentioning
confidence: 88%
“…These authors found that MFCs with sludge carbon electrodes, especially those obtained at a carbonization temperature of 1000 • C, exhibited improved performance in chemical oxygen demand removal efficiency, organic matter degradation, and electrochemical oxidation activity compared with carbon cloth electrodes. The sludge carbonization temperature significantly influenced MFC system voltage output, with sludge carbon electrodes consistently outperforming carbon cloth electrodes [177]. This can be seen in Figure 10.…”
Section: Microbial Fuel Cell Electrodesmentioning
confidence: 88%
“…Complex biofilms can consist of two cultures, the synergistic effect of which is well studied, or of dozens of different strains with extremely complex interactions. The most popular mixed crop used in MFCs to this day is active sludge [ 214 ]. However, its composition is constantly changing and difficult to reproduce, which means that it is impossible to fully predict the ways of processing substrates and the effectiveness of electronic transfer in each specific case.…”
Section: Mfc Based On Microbial Biofilmsmentioning
confidence: 99%
“…Efforts are on to improve efficiency and couple value-addition benefits to the bio-based treatment processes to realize their full potential for real-world applications 2 . Transforming organic compounds in wastewater into valuable derivatives using bioelectrochemical systems (BESs) has drawn advancing attraction due to its prospect in miscellaneous implementations 3 . Microbial fuel cell (MFC) is an attractive addendum to this biotechnological venture for their potential to break down the biodegradable organic compounds that exist in wastewater bodies using electroactive microbes and simultaneously generate bioelectrical power through bioelectrochemical transformation strategies 4 .…”
Section: Introductionmentioning
confidence: 99%